Efforts for Early Detection of Pregnant Women in Reducing AKI -AKB - Sumarmiati; Indasah (Journal of Global Research in Public Health, 2024)
The aim of the research is to determine efforts for early detection of pregnant women in reducing the IMR in the UPTD area of the Puncu Health Center, Puncu District, Kediri Regency. The research approach uses qualitative research. The research sample was pregnant women. The data analysis technique uses the USG method and SWOT analysis. The research results conclude: (1) The capabilities of posyandu cadres can be improved through empowerment (training) and establishing cadre recruitment criteria; (2) Knowledge of pregnant women can be increased through counseling and active involvement of posyandu cadres; (3) SOPs need to be created and disseminated to detect high risks for cadres; (4) Providing high risk early detection tools at each posyandu, and training cadres to be able to use these tools; (5) Determine the village bedan's activity schedule to provide consultations to cadres and add representative cadres according to the number of pregnant women served; (6) The government increases the budget allocation for cadre honorariums and provides bonuses to cadres who excel